Abdominal computed tomography findings in patients with exudative ascites - Fakhri, Rasha Th.; Muhi, Ahmed M.; Al-Hilli, Mohammed R.; Sulaiman, Tharwat I. (Journal of the Faculty of Medicine Baghdad, 2017)
Background: peritoneal cavity can be involved in inflammatory and malignant diseases and using computed tomography (CT) findings of exudative ascites may help in the differentiation. Objectives: 1-Describe CT features in patients with exudative ascites.2-Obtain useful CT findings to differentiate between tuberculous (TB) peritonitis and peritoneal carcinomatosis. Patients &methods: A cross sectional study conducted in Medical City Teaching Complex from September 2009 to September 2010 studied patients with exudative ascites using CT scan and confirmed later with histopathology examination. CT scan results were presented according to cytology examination and biochemical analysis. Results: 35 patients with exudative ascites were studied, including 19 males &16 females, age varied from 20 to73 years. While the amount of ascites(large or small) did not show statistically significant association with malignant disease, the density of ascitic fluid was slightly higher in TB[range(18-22)Hounsfield Unit(HU),mean is 20HU]compared to malignant ascites [range(15-20)HU ,mean is 18HU].Right subphrenic ascitic collections are associated with malignant disease (12 or 60% compared to 2 or 13.3% in TB) and pelvic ascitic collections were associated with TB disease (8 or 53.3% compared to 3 or 15% in malignant disease). Conclusion: In addition to omental cake &thickened bowel wall, malignant exudative ascites on CT scan is likely to have lower density, located in the right subphrenic space than in the pelvic region compared to benign (tuberculous) exudative ascites المقدمة :هذه الدراسة للتفريق بين مسببات الاستسقاء النضحي الحميدة والخبيثة باستخدام المفراس الحلزوني. الاهداف: وصف مشاهدات المفراس الحلزوني في الاستسقاء النضحي، استخدام مشاهدات المفراس الحلزوني للتفريق بين مسببات الاستسقاء النضحي الحميدة والخبيثة المرضى والطرائق: لقد تم دراسة 35 مريض يعانون من استسقاء البطن عن طريق الاختيار العشوائي للمرضى في وحدة المفراس لمستشفيات مدينة الطب التعليمية للفترة من ايلول 2009 الى ايلول 2010, وتم تأكيد النتيجة من الفحص المختبري,هؤلاء المرضى مكونين من 19 ذكر و16 أنثى .وكانت أعمار المرضى تتراوح بين 20-73. النتائج: وجدنا ان كثافة سائل الاستسقاء كانت مرتفعة عند مرضى التدرن البريتوني (20 وحدة هاونسفيلد) بالمقارنة مع المسسببات الخبيثة للاستسقاء النضحي (15 وحدة هاونسفيلد) يكون تجمع الاستسقاء في الناحية تحت الحجاب اليمنى في المسببات الخبيثة (12 او 60% بالمقارنة مع 2 او 13.3% في المسببات الحميدة ) والتجمع في الناحية الحوضية اكثر في مرضى التدرن (8 او 53.3% بالمقارنة مع 3 او 15 % في المسببات الخبيثة). الاستنتاج: اضافة الى الكعكة الثربية والتثخن في جدار الامعاء, يكون الاستسقاء النضحي ذو المسببات الخبيثة بكثافة اقل ويكثر تواجده في الناحية تحت الحجاب اليمنى بالمقارنة مع المسببات الحميدة للاستسقاء